External skeletel fixation in combination with intramedullary pinning for management of long bone fractures in dogs - Venkateswaralu B (Department of Veterinery surgery and Radiology, College of Veterinary and Animal Science, 2006)
Long bone fractures especially femur undergo rotational instability when treated with intramedullary pin alone and hence, managed with the combination technique including external skeletal fixation with intramedullary pin in eight dogs presented to the Surgery Units of Veterinary Hospitals, at Mannuthy and Kokkalai, College of Veterinary and Animal Sciences, Mannuthy, during the period from April 2005 to June 2006. All the animals were subjected to clinical, radiological, haematological and serum biochemical evaluation, both preoperatively and postoperatively and observations were recorded fortnightly, upto eight weeks. The selected patients were subjected to treatment with external skeletal fixation with intramedullary pin and acrylic connecting bar was used in animals which were below 15 kg body weight and stainless steel connecting bars in those animals which were above 15 kg body weight. Steinmann pin of suitable size that occupied 70% of the medullary cavity at the isthmus was selected and was found satisfactory in all animals except in one animal where mild angulation between the fracture fragments was observed in immediate postoperative radiograph. However, when the fracture gap got filled with sufficient callus, the straightness of the bone was restored to normal. There was satisfactory use of two pins or only one pin in a fragment, use of smooth pins, drilling all pins at almost parallel to each other, drilling pins through fracture line and fixing the connecting bar close to the skin leaving only one centimetre between skin . But one animal showed no evidence callus formation even by eighth postoperative week and resulted in nonunion due to old age. External fixator was stable in all animals except in two animals, where there was implant instability due to self mutilation. Satisfactory alignment and apposition between the fracture fragments were observed in most of the cases except one animal where the Cerclage wire was loosened and the tip of the intramedullary pin was found away from the medullary canal. Mild angulation between the fracture fragments noticed in one animal but appeared insignificant clinically and the straightness of the bone was restored to normal when the fracture gap got filled with sufficient callus. When compared to stainless steel connecting bar, acrylic connecting bar also provided adequate stability in femoral fracture repair of animals less than 15 kg body weight and provided cheaper alternative to the former as it does not require the expensive components. But, due to the innate nature of a animal in one animal, the acrylic connecting column was broken by self mutilation and after the reapplication of the acrylic connecting column, the fracture stability attained was satisfactory and showed progressive improvement in limb usage from sixth postoperative. All the animals except in four animals had functional limb usage on the third postoperative day following combination technique of external skeletal fixation with intramedullary pin. Young growing animals under the study showed rapid callus formation and good radiographic union when compared to old animals. One animal showed no evidence of callus formation even by eighth week which resulted in nonunion. Complications commonly observed in the combination technique of external skeletal fixation with intramedullary pinning were quadriceps muscle contracture and stifle stiffness. This was obviously observed in young growing animals below one years of age. The combination technique of external skeletal fixation with intramedullary pinning in the animals studied was effective in countering the rotational and bending forces acting on the long bones, especially the femur. This provided early return of functional limb usage with good radiographic and clinical union.